2012
DOI: 10.4236/as.2012.34066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pathogencity and race classification of <i>Xanthomonas oryzae</i> pv. <i>oryzae</i> in guilan province-Iran

Abstract: To evaluation of pathogenicity and race classification of Xanthomonas oryzae pv. oryzae agent bacterial leaf blight of rice, 153 isolates of X. oryzae pv. oryzae were collected from different rice-growing cities of Guilan province-Iran. All of isolates were inoculated to assess the differential characteristics of 26 near isogenic rice lines containing a single resistance gene or two to five genes. Inoculation was done 21 days after sowing in the greenhouse. Scoring of inoculated plants was done 18 days after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…In this study, we establish the level of resistance to the bacterial blight pathogen conferred by a single gene individually and multiple gene combinations. Previous results on the basis of host-pathogen interaction showed that there were four bacterial leaf blight races in Iran [28]. These races were tested on 12 international differentials of near-isogenic lines and 14 varieties of pyramided lines and 8 local and improved varieties to support a gene deployment approach to managing the disease using resistant cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we establish the level of resistance to the bacterial blight pathogen conferred by a single gene individually and multiple gene combinations. Previous results on the basis of host-pathogen interaction showed that there were four bacterial leaf blight races in Iran [28]. These races were tested on 12 international differentials of near-isogenic lines and 14 varieties of pyramided lines and 8 local and improved varieties to support a gene deployment approach to managing the disease using resistant cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…In Guilan province, previous results on BLB showed that there were four races of X. oryzae pv. oryzae [28]. The purpose of this study is to identify resistance sources for controlling the rice bacterial blight in Guilan-Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Galur isogenik bermanfaat dalam monitoring keparahan serangan dan distribusi ras Xoo (Ogawa et al, 1988). Di samping itu, galur-galur isogenik juga dapat digunakan sebagai standar diferensial untuk mengetahui perbedaan respons patogenisitas atau virulensi suatu ras (Hayashi dan Fukuta, 2007;Khoshkdaman et al, 2012;Loan et al, 2006;Noh et al, 2016;Tsunematsu et al, 2000) dan untuk evaluasi ketahanan galur hasil persilangan (silang balik) dalam rangka perakitan varietas tahan HDB (Webb et al, 2010).…”
Section: Pendahuluanunclassified
“…Near isogenic lines (NILs) with specific resistance genes have been identified and among them, lines with a single resistance gene are widely used to characterize virulence and differentiate pathogenic races of Xoo. Classification of the pathogenic race of Xoo is based on the interaction between its avr gene and rice Xa gene [23,[26][27][28]. In this study, we used IRBB4 line carrying Xa4 gene and the susceptible genotype FKR14.…”
Section: Strain Virulencementioning
confidence: 99%
“…The phenotypic reactions of the bacteria strains and rice line IRBB4 were similar to the reaction observed on FKR14 except with strain Mai1. IRBB4 line shows susceptibility to Xoo strains from Iran [28], while in China; it is susceptible to 50% of Chinese Xoo strains [29]. In earlier 1970, the Xoo populations were dominated by those strains that could not infect rice lines with Xa4 gene [30], while the newly developed rice lines with Xa4 gene are nowadays susceptible to several strains [31].…”
Section: Strain Virulencementioning
confidence: 99%